Issues of Legal Regulation and Administration of the National Security Concept of the Armenian Republic Between 1990-1995 - Vagharshyan , A. (Bulletin of Yerevan University C: Jurisprudence, 2018)
Strategic planning of national security, its legal entrenchment and administration is one of the most important tasks of the state. Within the system of state functions the provision of national security is not a separate function; rather it is an inter-functional issue, an important one of pivotal importance, which relates to all the objectives of state functions and has inner and outer components. The analysis of legal policy confirms that after the independence of the Republic of Armenia, between 1991-1995 there was no security-based normative regulation of the state and legal system; neither on legislative nor on by-laws levels. The presidential governance form secured the relatively quick and operative solution for daily administrative problems, but it didn’t transform to a strategic planning and administration system based on a security concept.